Bottom‐up processes mediated by social systems drive demographic traits of coral‐reef fishes. Issue 3 (23rd January 2018) - Taylor, Brett M.; Brandl, Simon J.; Kapur, Maia; Robbins, William D.; Johnson, Garrett; Huveneers, Charlie; Renaud, Phil; Choat, John Howard
Abstract: Ectotherms exhibit considerable plasticity in their life‐history traits. This plasticity can reflect variability in environmental and social factors, but the causes of observed patterns are often obscured with increasing spatial scales. We surveyed dichromatic parrotfishes across the northern Great Barrier Reef to examine variation in body size distributions and concomitant size at sex change ( L ∆50 ) against hypotheses of directional influence from biotic and abiotic factors known to affect demography. By integrating top‐down, horizontal, and bottom‐up processes, we demonstrate a strong association between exposure regimes (which are known to influence nutritional ecology and mating systems) and both body size distribution and L ∆50 (median length at female‐to‐male sex change), with an accompanying lack of strong empirical support for other biotic drivers previously hypothesized to affect body size distributions. Across sites, body size was predictably linked to variation in temperature and productivity, but the strongest predictor was whether subpopulations occurred at sheltered mid and inner shelf reefs or at wave‐exposed outer shelf reef systems. Upon accounting for the underlying influence of body size distribution, this habitat‐exposure gradient was highly associated with further L ∆50 variation across species, demonstrating that differences in mating systems across exposure gradients affect the timing of sex change beyond variation concomitant with differing overall body sizes. We posit that exposure‐driven differences in habitat disturbance regimes have marked effects on the nutritional ecology of parrotfishes, leading to size‐related variation in mating systems, which underpin the observed patterns. Our results call for better integration of life‐history, social factors, and ecosystem processes to foster an improved understanding of complex ecosystems such as coral reefs.